2008
DOI: 10.1016/j.gie.2007.08.044
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a classification for methylene blue magnification chromoendoscopy in premalignant gastric lesions

Abstract: Background: Conventional endoscopy has low sensitivity, specificity, and interobserver agreement for the diagnosis of gastric atrophy, intestinal metaplasia, and dysplasia. Magnification chromoendoscopy (ME) may optimize the evaluation of premalignant gastric lesions.Objective and Design: As part of a multicenter trial, we aimed at validating a previously proposed classification for gastric methylene blue ME at a different center.Setting, Patients, and Interventions: A sample of patients (n Z 42) with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 37 publications
1
38
0
1
Order By: Relevance
“…This prescribes a considerable effort in order to evaluate the risk of the patient for the development of gastric cancer. Magnification chromoendoscopy may optimize the evaluation of premalignant gastric lesions (Areia et al, 2008). Topographic mapping for the detection of extensive intestinal metaplasia or more advanced lesions such as dysplasia or carcinoma should be consider when evaluating the patient's risk (Correa et al, 2010).…”
Section: Premalignant Lesions: Intestinal Metaplasia Low-grade Dysplmentioning
confidence: 99%
“…This prescribes a considerable effort in order to evaluate the risk of the patient for the development of gastric cancer. Magnification chromoendoscopy may optimize the evaluation of premalignant gastric lesions (Areia et al, 2008). Topographic mapping for the detection of extensive intestinal metaplasia or more advanced lesions such as dysplasia or carcinoma should be consider when evaluating the patient's risk (Correa et al, 2010).…”
Section: Premalignant Lesions: Intestinal Metaplasia Low-grade Dysplmentioning
confidence: 99%
“…[4] However, early detection of gastric dysplasia renders a great challenge to the endoscopists as these flat lesions are usually lack of obvious gross morphological changes to be visualized under conventional white-light endoscopy. [5] In the past decade, Raman spectroscopy, which measures inelastic light scattering processes and is capable of providing specific spectroscopic fingerprints of molecular compositions and structures of biological tissues, has been comprehensively investigated for precancer and cancer diagnosis and evaluation. [6 -22] Under near-infrared (NIR) laser light excitation, the resulting NIR Raman spectroscopy holds significant advantages in that water exhibits very low absorption at the working wavelength range, and tissues exhibit far less autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Dinis-Ribeiro et al [9] showed that it was possible to effectively diagnose certain gastric lesions (namely extension of intestinal metaplasia in the gastric mucosa) and adequately predict neoplasia occurrence using this technology. Dinis-Ribeiro developed an original classification for gastric mucosa, recently externally validated [10], dividing images into 3 groups based on their colour and texture features, which were proven to be robust in intra-observer and inter-observer evaluation. A future objective of our research is to automate this classification, based on the promising results of the study presented here.…”
Section: Methodsmentioning
confidence: 99%